Ischaemic preconditioning reduces troponin T release in patients undergoing coronary artery bypass surgery. - Jenkins, D. P. (1997)
OBJECTIVE: To investigate whether ischaemic preconditioning could reduce myocardial injury, as manifest by troponin T release, in patients undergoing elective coronary artery bypass surgery. DESIGN: Randomised controlled trial. SETTING: Cardiothoracic unit of a tertiary care centre. PATIENTS: Patients with three vessel coronary artery disease and stable angina admitted for first time elective coronary artery bypass surgery were invited to take part in the study; 33 patients were randomised into control or preconditioning groups. INTERVENTION: Patients in the preconditioning group were exposed to two additional three minute periods of myocardial ischaemia at the beginning of the revascularisation operation, before the ischaemic period used for the first coronary artery bypass graft distal anastomosis. MAIN OUTCOME MEASURE: Serum troponin T concentration at 72 hours after cardiopulmonary bypass. RESULTS: The troponin T assays were performed by blinded observers at a different hospital. All patients had undetectable serum troponin T (< 0.1 microgram/l) before cardiopulmonary bypass, and troponin T was raised postoperatively in all patients. At 72 hours, serum troponin T was lower (P = 0.05) in the preconditioned group (median 0.3 microgram/l) than in the control group (median 1.4 micrograms/l). CONCLUSIONS: The direct application of a preconditioning stimulus in clinical practice has been shown, for the first time, to protect patients against irreversible myocyte injury.